1990
DOI: 10.1177/036354659001800315
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of a prophylactic knee brace to reduce knee injuries in football

Abstract: The purpose of this prospective, randomized study was to determine the efficacy of a prophylactic knee brace to reduce the frequency and severity of acute knee injuries in football in an athletic environment in which the athletic shoe, playing surface, athlete-exposure, knee injury history, and brace assignment were either statistically or experimentally controlled. The participants in the study were 1396 cadets at the United States Military Academy, West Point, New York, who experienced a total of 21,570 athl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
1
3

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(104 citation statements)
references
References 11 publications
3
97
1
3
Order By: Relevance
“…One level I randomized controlled trial on 1396 military cadets participating in intramural tackle football (26) showed significant differences between braced and unbraced groups. This supports the use of PKB in American football players, reducing medial collateral ligament injuries and overall knee injuries (P < 0.05).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…One level I randomized controlled trial on 1396 military cadets participating in intramural tackle football (26) showed significant differences between braced and unbraced groups. This supports the use of PKB in American football players, reducing medial collateral ligament injuries and overall knee injuries (P < 0.05).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…[18][19][20][21][22][23][24] A meta-analysis was not prudent for summarizing these data because outcomes, braces used, and injury inclusion criteria were different for all the studies.…”
Section: Included Studies and Quality Assessmentmentioning
confidence: 99%
“…Prophylactic knee braces [15][16][17] are braces with unilateral or bilateral bars, hinges, and adhesive straps. The deformable metal of these braces can absorb some of the impact and decrease the force applied to the medial collateral ligament by 10% to 30%.…”
Section: Prophylactic Knee Bracesmentioning
confidence: 99%
“…Despite anecdotal reports of success, scientific studies have not universally shown that prophylactic knee braces significantly reduce knee injuries. [15][16][17][18] Thus, there is insufficient evidence to recommend prophylactic knee bracing in the young athlete. [1][2][3]7,[15][16][17][18] …”
Section: Prophylactic Knee Bracesmentioning
confidence: 99%